2020
DOI: 10.1016/j.clinph.2020.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis weakens spinal recurrent inhibition and post-activation depression

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 68 publications
(69 reference statements)
1
15
0
Order By: Relevance
“…Their results in ALS patients are consistent with our observations that the inhibition can be within the normal range or decreased according to the level of lower limb disabilities. Accordingly, Özyurt et al 37 and the present study allow to reconsider the possible role of Renshaw cells in ALS.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Their results in ALS patients are consistent with our observations that the inhibition can be within the normal range or decreased according to the level of lower limb disabilities. Accordingly, Özyurt et al 37 and the present study allow to reconsider the possible role of Renshaw cells in ALS.…”
Section: Discussionmentioning
confidence: 51%
“…Accordingly, the possible alteration of recurrent inhibition and the implication of Renshaw cells in ALS has been quite rightly questioned 34 . However, a recent study has shown that the inhibitory period in peristimulus frequencygram (PSF) of single motor units is shortened in lumbar‐affected ALS patients but unchanged in nonlumbar‐affected ones 37 . The authors, who developed the method, have argued that this inhibition is mostly due to recurrent inhibition of soleus LMNs produced by stimulation of PTN in the lateral part of the popliteal fossa, which primarily produces M response in soleus EMG 80,81 .…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of glycinergic receptor binding in the anterior gray matter of the spinal cord (Hayashi et al, 1981; Whitehouse et al, 1983) has been demonstrated along with abnormal glycine and gamma amino butyric acid (GABA) levels in blood serum (Malessa et al, 1991; Niebroj-Dobosz and Janik, 1999). Electrophysiology also suggests disruption in spinal inhibitory circuits in ALS patients (Raynor and Shefner, 1994; Shefner and Logigian, 1998; Sangari et al, 2016; Özyurt et al, 2020). An interesting question is whether the neurons are altered in excitability only within the motor circuit (i.e., corticospinal neurons and the synaptically-connected spinal inhibitory and cholinergic interneurons, and MNs), or if disturbances are more widespread throughout the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, no studies thus far have directly assessed activity of spinal premotor interneurons in an ALS model. Despite evidence that ALS patients have disrupted inhibition at spinal levels (Raynor and Shefner, 1994;Shefner and Logigian, 1998;Sangari et al, 2016;Howells et al, 2020;Özyurt et al, 2020), much is still unknown concerning the involvement of inhibitory circuitry in ALS. Morphological alterations in inhibitory circuits have been demonstrated in animal models of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study performed by Özyurt et al compared spinal recurrent inhibition and postactivation depression (PAD) on the soleus muscle in lumbar-affected and nonlumbar-affected ALS patients (157). PAD is another spinal circuit with an effective presynaptic network that tones down the output of the primary afferents on motoneurons.…”
Section: Recurrent and Cortical Inhibitionmentioning
confidence: 99%